A PETROLOGICAL AND GEOCHEMICAL STUDY OF THE VOLCANIC ROCKS OF THE CROWSNEST FORMATION, SOUTHWESTERN ALBERTA, AND OF THE HOWELL CREEK SUITE, BRITISH COLUMBIA - Bowerman M.; Christianson A.; Creaser R.A.; Luth R.W. (My University, 2006)
Alkaline igneous rocks of the Crowsnest Formation in southwestern Alberta and in the Howell Creek area in southeastern British Columbia have been suggested previously to be cogenetic. To test this hypothesis, samples of both suites were characterized petrographically and their major and trace element geochemistry was determined. A subset of the samples was analyzed for whole-rock Sr and Nd isotope geochemistry. The samples of the two suites are latites, trachytes, and phonolites based on the International Union of Geological Sciences (IUGS) total alkalis versus silica (TAS) diagram. Samples from both suites show similar patterns on mantle-normalized trace element diagrams, being enriched relative to mantle values but depleted in the high field-strength elements Nb, Ta, and Ti relative to the large-ion lithophile elements. The chondrite-normalized rare-earth element (REE) patterns for both suites are light REE enriched, with no Eu anomaly and flat heavy REE. The isotope geochemistry of both suites is characterized by low initial 87Sr/86Sr (SrT = 0.704 to 0.706) and low εNdT (-7 to -16). The Howell Creek samples have lower εNdT and higher SτT than do the Crowsnest samples. Based on the intra- and intersuite differences in the isotope geochemistry, we conclude that these samples are not cogenetic, but rather represent samples that have experienced similar evolutionary histories from a heterogeneous source region in the subcontinental lithospheric mantle. © 2006 NRC Canada.